Trust Model In Online Information Of Smart Government: A Conceptual Framework - Mohammad Thaiban, Hasan Hamdan; Kamalrudin, Massila; Al-Shami, Samer Ali Hussein; Hakimi, Halimaton Saadiah; Sidek, Safiah; Akmal, Suriati (The Mattingley Publishing Co., Inc, 2020)
Online information has gained significant importance in management and holds great value creation potential for public services. A pressing issue in this regard is how public organization can adapt their traditional structures and processes to the innovative field of online information to create public trust. This study aims to provide a new trust model of online information in smart government system to improve the public trust.The proposed conceptual model for evaluating publics’ acceptance to use online information constructs from Technology Acceptance Model. The proposed model will improve the service delivery of UAE government departments by enhancing the trust of public towards the online information usage.